High-frequency electrical stimulation promotes reshaping of the functional connections and synaptic plasticity in in vitro cortical networks. (17th October 2018) - Poli, Daniele; Massobrio, Paolo
Abstract: High-frequency electrical stimulation (tetanus) promotes global synaptic potentiation in dissociated cortical networks coupled to multi-electrode arrays (MEAs). Since little is known about the functional changes induced by this protocol, this work aims to investigate the statistical dependences between the time series (i.e. functional links) of the network nodes involved pre- and post-tetanus. Specifically, we first show a strong reshaping of the functional connections induced by the stimulation and possibly associated with the global plasticity. Then, we find that about 30% of the nodes linked before and after electrical perturbation show high-connectivity degree (⩾9 links), occupying a central role in the neuronal communication. Finally, we observe that these functional units drive the global network plasticity showing more synaptic potentiation than the other nodes involved in the connectivity reshaping.